In the valleys of the noble beyond : in search of the Sasquatch - Zada, John (Atlantic Monthly Press, 2019)
On the central coast of British Columbia, the Great Bear Rainforest is part of the largest temperate rainforest in the world; for centuries people have reported encounters with the Sasquatch.